PENGARUH PROSES REKRUTMEN DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MOST BLUE RESORT & SPA GIANYAR - Herlambang, Putu Gede Denny; Sumerta, I Komang; Sukanti, Ni Ketut; Indrawati, Ni Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to determine the influence of recruitment and training on employee performance. Sampling method using saturated sample. Data were collected using the method of observation, interviews, and quitionaires. Respondents of the study by 55 employees at the PT. Most Blue Resort and Spa. The data analysis techniques used are quantitative and qualitative analyses. The program were used to perform data analysis is SPSS version 22 for Windows. These results indicate that recruitmen effect on employee performance at  the PT. Most Blue Resort and Spa. Training effect on employee performance at  the PT. Most Blue Resort and Spa. Recruitment and training has a positive affect on employee performance at  the PT. Most Blue Resort and Spa.